2017
DOI: 10.1113/jp274887
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency accelerates ageing and age‐related diseases: a novel hypothesis

Abstract: Ageing can occur at different rates, but what controls this variable rate is unknown. Here I have developed a hypothesis that vitamin D may act to control the rate of ageing. The basis of this hypothesis emerged from studyng the various cellular processes that control ageing. These processes such as autophagy, mitochondrial dysfunction, inflammation, oxidative stress, epigenetic changes, DNA disorders and alterations in Ca and reactive oxygen species (ROS) signalling are all known to be regulated by vitamin D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 195 publications
2
85
0
1
Order By: Relevance
“…Vitamin D has also been linked to distinct components of the ageing process ( Figure 2). The negative acute phase reactant vitamin D [90] mitigates oxidative stress at least in part through increased expression of anti-oxidant regulators, including NRF2 and klotho [91][92][93]. Thus, calcitriol increased renal and circulating klotho expression, whereas it reduced markers of oxidative stress in uninephrectomized, spontaneously hypertensive rats [94].…”
Section: The Endocrine Phosphate-fgf-23-klotho Axis and Premature Agementioning
confidence: 99%
“…Vitamin D has also been linked to distinct components of the ageing process ( Figure 2). The negative acute phase reactant vitamin D [90] mitigates oxidative stress at least in part through increased expression of anti-oxidant regulators, including NRF2 and klotho [91][92][93]. Thus, calcitriol increased renal and circulating klotho expression, whereas it reduced markers of oxidative stress in uninephrectomized, spontaneously hypertensive rats [94].…”
Section: The Endocrine Phosphate-fgf-23-klotho Axis and Premature Agementioning
confidence: 99%
“…Therefore, those who have vitamin D deficiency are usually more susceptible to suffering from different pathologies associated with age such as Parkinson's disease, Alzheimer's, and cardiovascular disease, among others. On the other hand, subjects with normal plasma levels of vitamin D are generally less likely to suffer any of the diseases mentioned [103][104][105]. It has also been indicated that vitamin D deficiency is related to a decrease in the expression of VDR and an altered activity of antioxidant enzymes at the skeletal muscle level.…”
Section: Effects Of Vitamin D In the Attenuation Of Mitochondrial Oximentioning
confidence: 99%
“…Epidermal AMPs like cathelicidin (hBD18) expressed in keratinocytes is induced by 1,25 (OH) 2 vitamin D3 from 7-dehydrocholesterol and protects the skin against pathogens ( 8 , 206 , 207 ). Vitamin D promotes autophagy (ATG16L1 in autoimmune disorders like inflammatory bowel disorder) and suppresses pro-inflammatory pathways (such as p38 MAPK-mediated signaling pathway, prostaglandin pathway, nuclear factor kappa B signaling pathway) ( 206 , 208 , 209 ).…”
Section: Skin Exposures and Autophagymentioning
confidence: 99%